The Effect of Using an Electronic Instructional Game in Improving English Language Vocabulary for Third Graders in Irbid City - Alsharafat, W.; Alrashdan, Wesam Kurdi; Bani Younes, Mohammad (International Journal of Interactive Mobile Technologies (iJIM), 2017)
This study aims to investigate the effect of using an educational computer game on the improvement of learning English language vocabulary in the city of Irbid. To achieve this aim was programmed a computer game to teach third graders English language vocabulary. The sample of the study consisted of 97 male and female students. They deliberately selected from Kofor Awaan Girls School and Abu Isam Primary Boys School, they were distributed over two groups: One of them is an experimental group of 52 students (male, female) taught English language vocabulary through a computer game strategy, and the other a control group of 47 students (male, female). The findings of the study showed that there are statistical significant differences at the level of (α=0.05) between the experimental group and the control group in favour of the experimental group, and that there are statistical significant differences at the level of (α=0.05) related to gender in favour of female, and that there are statistical significant differences at the level of (α=0.05) of the interaction between the teaching strategy and gender.